وسيلة Power Point Interaktif وفعاليتها لترقية قدرة الطالبات على فهم النعت والمنعوت بـ SMP Plus Maryam Binti Ibrahim Aceh Besar - Fajriah Fajriah; Nurlela Nurlela ('ARABIYYA: JURNAL STUDI BAHASA ARAB, 2025)
The problem at SMP Plus Maryam Binti Ibrahim Aceh Besar is that  the students are not able to understand Na’at and Man’ut . This research aims to identify the effectiveness the use of Interactive Power Point media to increase students’  ability to understand Na’at and Man’ut . The research method in this research is pre experimental method with the one group pre-test and post-test design. To collect the data, the researcher used the test . The result of this research is the using of Interactive Power Point media is effective to increase students’  ability to understand Na’at and Man’ut. Furthermore, it was found that the result of the T-Test is a significance level (2- tailed) 0.00<0.05. This value shows that the alternative hypothesis (Ha) is accepted and the null hypothesis (H0) is rejected.